Element composition of sediment core EN21103 from Lake Ulu, eastern Siberia - Jia, Weihan; Biskaborn, Boris K; Stoof-Leichsenring, Kathleen Rosmarie; Marent, Andreas; Weiner, Mikaela; Meyer, Hanno; Pestryakova, Luidmila A; Herzschuh, Ulrike (In: Jia, W et al. (2024): Geochemistry of sediment core EN21103 from Lake Ulu, eastern Siberia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.965485, 2024)
Element composition including total carbon (TC), total organic carbon (TOC), total inorganic carbon (TIC), and total nitrogen (TN), measured with a soli TOC cube (Elementar) and a rapid MAX N exceed (Elementar) at the Carbon and Nitrogen Laboratory of AWI in Potsdam. The minimum detectable concentration for natural sediment samples is 0.1% for both machines.
Keywords: Geochemical proxies; Lake sediment core; Lake Ulu; Oymyakon; radiocarbon age; Siberia; TC; TIC; TN; TOC